Practical approach to quantification of mRNA abundance using RT-qPCR, normalization of experimental data and MIQE - Obolenskaya, M.Yu.; Kuklin, A.V.; Rodrigez, R.R.; Martsenyuk, O.P.; Korneyeva, K.L.; Docenko, V.A.; Draguschenko, O.O. (Вiopolymers and Cell, 2016)
Reverse transcription and quantitative polymerase chain reaction (RT-qPCR) has become the most common method for characterizing expression patterns of individual mRNAs due to a large dynamic range of linear quantification, high speed, sensitivity, resolution and cost-effectiveness. However, the complexity of the protocol, variability of reagents, an inconsistent quality of biological samples, and the absence of standardized methods of data quantification may produce inconsistent results. In an effort to to standardize ithe procedure and assure high reliability of data, the minimum information for publication of quantitative real-time PCR experiments (MIQE) guidelines was defined and further extended by Prof. Bustin and colleagues (2004). These guidelines have been followed by the development of an XML-based real-time PCR data markup language (RDML) and a RDML data base for consistent reporting of RT-qPCR data created by the RDML consortium. Here we follow the RT-qPCR procedure step by step in compliance with MIQE requirements, local facilities and resources and our own experience in application of RT-qPCR methodology. Реакція зворотної транскрипції і ланцюгової полімеризації в реальному часі (ЗТ-кПЛР) стала найбільш уживаним методом для характеристики профілів експресії індивідуальних мРНК через можливості оцінки концентрацій в широкому діапазоні, відносної швидкості реакції, чутливості, роздільності і відносно невеликої вартості. Однак, багатоступеневий характер реакції, різні реактиви, різна якість біологічних зразків і відсутність стандартних приписів для проведення реакції приховують небезпеку отримати викривлені результати. Для стандартизації кожного з етапів методу і підвищення надійності результатів проф. С. Бустіним із співробітниками [2004] була розроблена методична інструкція, що містила мінімальну інформацію, яка необхідна для публікації результатів, отриманих за допомогою ЗТ-кПЛР. Крім того, RDML консорціумом на основі XML ( розширювана мова розмічання) створені спеціальна мова RDML і база даних RDML для збору і аналізу результатів ЗТ-кПЛР экспериментів. В цій статті ми описуємо весь процес ЗТ-кПЛР по етапах згідно вимог методичної інструкції MIQE і нашим власним досвідом у застосуванні цього методу. Реакция обратной транскрипции и количественной цепной полимеризации (ОТ-кПЦР) стала наиболее используемым методом для характеристики профиля экспрессии индивидуальных мРНК благодаря широкому диапазону измеряемых концентраций, малой затратности по времени исполнения, чувствительности, разрешающей способности и относительно небольшой стоимости. Однако, многоступенчатый характер реакции, разнообразие используемых реактивов, разное качество биологических образцов и отсутствие стандартных подходов для количественной оценки результатов таит опасность получить искаженные результаты. Для максимальной стандартизации каждого из этапов реакции и повышения надежности результатов проф. С. Бустиным с сотрудниками [2004] была разработана методическая инструкция с указанием минимальной информации (MIQE), необходимой для публикации данных, которые были получены с помощью ОТ-кПЦР. Кроме того, RDML консорциумом на основе XML (расширяемый язык разметки) разработан специальный язык RDML и создана база данных RDML для сбора и анализа результатов ОТ-кПЦР экспериментов. В этой статье мы описываем поэтапно весь процесс ОТ-кПЦР в соответствии с требованиями методической инструкции MIQE и нашим опытом в области применения этого метода.